Gastric intraepithelial neoplasia in a Western population - Raftopoulos, S.; Kumarasinghe, P.; de Boer, B.; Iacobelli, J.; Kontorinis, N.; Fermoyle, S.; Olynyk, John; Forrest, C.; Ee, H.; Yusoff, I. (Lippincott Williams & Wilkins, 2012)
Background and study aims: Descriptions of the natural history and endoscopic appearances of gastric dysplasia/ intraepithelial neoplasia (IEN) that originate mainly from Europe. Currently, there are no Australian data available. We aimed to document endoscopic appearances and progression rates of gastric IEN and to determine the significance of indefinite for IEN. Patients and methods: This is a retrospective study, in which cases diagnosed with gastric IEN were identified between 2000 and 2009. Endoscopic appearances, progression rates to more advanced IEN or cancer, and long-term outcomes were recorded. Results: A total of 160 cases with IEN (26.9% high grade, 57.5% low grade, 15.6% indefinite) were identified. The mean age was 67.8 years and 53.8% were men. Endoscopic lesions were polypoid in 29.4% and nonpolypoid in 70.6%. The most common location was the antrum (58.7%). Forty patients had an intervention and 76 underwent endoscopic follow-up only. Twenty-two cancers were diagnosed; three who had an intervention were diagnosed within 12 months, one with low-grade intraepithelial neoplasia developing a cancer after 9.9 years, and 13 undergoing surveillance only, were diagnosed with cancer within 12 months of index endoscopy. Five cases had cancer after a mean of 2.6 years. Forty-seven cases initially labelled as indefinite; following rereview 25 remained unchanged, 11 reclassified as negative for IEN, 10 as low grade, and one as high grade. Three of these cases developed cancer over the study period. Conclusion: We concluded that (a) majority of gastric IEN are associated with endoscopic lesions, (b) high rate of early cancer diagnosis was observed (c) rates of progression to cancer were lower than reported rates, and (d) indefinite for IEN is not innocuous requiring an expert pathologist’s review.